Menggagas Fiqh Perempuan: Membangun Kekuatan Hukum Bagi Perempuan (Telaah Kritis Atas Pemikiran Kh. Husein Muhammad) - Abd. Warits (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
The study on the relationship between women and men will never fade. This issue is always interesting as the various development issues era. Studie of Gender basically don't attempt to give birth to the women